Syringe access for the prevention of blood borne infections among injection drug users - Rich Josiah D; Agins Bruce; Stancliff Sharon; Burris Scott (BMC, 2003)
Abstract Background Approximately one-third of acquired immunodeficiency syndrome cases in the United States are associated with the practice of sharing of injection equipment and are preventable through the once-only use of syringes, needles and other injection equipment. Discussion Sterile syringes may be obtained legally by 4 methods depending on the state. They may be purchased over the counter, prescribed, obtained at syringe exchange programs or furnished by authorized agencies. Each of these avenues has advantages and disadvantages; therefore, legal access through all means is the most likely way to promote the use of sterile syringes. Summary By assisting illicit drug injectors to obtain sterile syringes the primary care provider is able to reduce the incidence of blood borne infections, and educate patients about safe syringe disposal. The provider is also able to initiate discussion about drug use in a nonjudgmental manner and to offer care to patients who are not yet ready to consider drug treatment.